2020
DOI: 10.7759/cureus.11853
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Its Association With Quality of Life Among Hypertensive Patients Attending Primary Health Care Centers in Saudi Arabia

Abstract: Background Chronic diseases require long-term medication and adherence to medication is important for the control of disease as well as prevention of complications. Non-compliance may lead to worsening of the disease, which may affect patients' quality of life. This study aimed to assess the level of medication adherence and its association with quality of life (QOL) among hypertensive patients in Buraidah, Saudi Arabia. Methods A cross-sectional study was carried out in which 299 hypertensive patients were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
5
2
Order By: Relevance
“…In contrast to our findings, a study conducted in Spain found no relationship between polypharmacy and adherence [15]. On the other hand, a study in Saudi Arabia reported findings similar to ours regarding a relationship that exists between polypharmacy and level of adherence [12]. Family physicians can play an important role in increasing medication adherence among patients having comorbidities with polypharmacy by prescribing the most appropriate medications and avoiding those that are unnecessary.…”
Section: Identification Of Patient Characteristics and Other Factors ...contrasting
confidence: 88%
See 1 more Smart Citation
“…In contrast to our findings, a study conducted in Spain found no relationship between polypharmacy and adherence [15]. On the other hand, a study in Saudi Arabia reported findings similar to ours regarding a relationship that exists between polypharmacy and level of adherence [12]. Family physicians can play an important role in increasing medication adherence among patients having comorbidities with polypharmacy by prescribing the most appropriate medications and avoiding those that are unnecessary.…”
Section: Identification Of Patient Characteristics and Other Factors ...contrasting
confidence: 88%
“…The global rate of poor adherence is 46.6% [11]. A study on adherence to hypertension medication in Alsaqabi, Saudi Arabia, found that 38.8% of patients did not adhere to the prescribed medication regimen [12]. Another factor that may contribute to nonadherence is a lack of social support, having someone to talk to or ask for help, such as a family member, friend, or neighbor [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lower HRQoL affects medication adherence, which is important for managing hypertension (Holt et al, 2010 ). Overall, poor HRQoL is related to severe hypertension (Alsaqabi & Rabbani, 2020 ). The bidirectional associations between hypertension and HRQoL may lead to a vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, adherence to antihypertensive medications is essential for reducing blood pressure levels (Muntner et al, 2022 ). Uncontrolled hypertension is associated with nonadherence to the medication, such as improper dosage or frequency of medication (Alsaqabi & Rabbani, 2020 ). Low adherence to antihypertensive medication is a noteworthy barrier in managing hypertension (Holt et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 Poor medication adherence among NCD patients has been consistently associated with poor perceived overall quality of life (QOL) and poor satisfaction with health. [5][6][7][8] The WHO framework on adherence to long-term therapies identifies several factors that can influence adherence, including social and economic factors, the health-care team/system, the characteristics of the disease and disease therapies, and patient-related factors. 4 There are various ways to measure medication adherence, including self-report methods (e.g., scales like the Morisky Medication Adherence Scale and Visual Analogue Scale), electronic medication monitoring, pill count, electronic medical records, pharmacy claims, and prescription refill records.…”
mentioning
confidence: 99%